Fenomena Human Trafficking Ditinjau Dari Peranan Sosial Budaya Dan Media Massa - Eka Wahyu Hidayat (Jurnal Communicate, 2020)
This study aims to determine the phenomenon of human trafficking as a manifestation of adolescent sexual exploitation in Indonesia, which is seen from the point of view of the socio-cultural and mass media role. The method used in this study is a case study with secondary data. The results showed that the phenomenon of human trafficking can occur due to various factors (internal and external factors), mainly social and cultural factors adolescents and mass media.